2018
DOI: 10.1515/chem-2018-0014
|View full text |Cite
|
Sign up to set email alerts
|

DSC, FT-IR, NIR, NIR-PCA and NIR-ANOVA for determination of chemical stability of diuretic drugs: impact of excipients

Abstract: It is well known that drugs can directly react with excipients. In addition, excipients can be a source of impurities that either directly react with drugs or catalyze their degradation. Thus, binary mixtures of three diuretics, torasemide, furosemide and amiloride with different excipients, i.e. citric acid anhydrous, povidone K25 (PVP), magnesium stearate (Mg stearate), lactose, D-mannitol, glycine, calcium hydrogen phosphate anhydrous (CaHPO4) and starch, were examined to detect interactions. High temperatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…The major thermal transitions of all compounds are presented in Table 2 , including the thermal behavior of MIRCAP CT 85-H. When compared to pure citric acid [ 32 ], MIRCAP CT 85-H DSC curve presents two extra peaks, at 58.6 °C and 420.9 °C, attributed to the melting and decomposition, respectively, of hydrogenated palm oil used in the encapsulation process. It was also observed that due to the presence of hydrogenated palm oil, the citric acid decomposition of MIRCAP CT 85-H started approximately 10 °C above the decomposition temperature of pure citric acid.…”
Section: Resultsmentioning
confidence: 99%
“…The major thermal transitions of all compounds are presented in Table 2 , including the thermal behavior of MIRCAP CT 85-H. When compared to pure citric acid [ 32 ], MIRCAP CT 85-H DSC curve presents two extra peaks, at 58.6 °C and 420.9 °C, attributed to the melting and decomposition, respectively, of hydrogenated palm oil used in the encapsulation process. It was also observed that due to the presence of hydrogenated palm oil, the citric acid decomposition of MIRCAP CT 85-H started approximately 10 °C above the decomposition temperature of pure citric acid.…”
Section: Resultsmentioning
confidence: 99%
“…It was observed that the two endothermic peaks of the physical mixture sample showed significant inconsistency with samples before the mixing. Such broadening observed in the physical mixture spectrum may be due to the interactions between the hydrogen bonding between OH (hydrogen donor) of starch, and hydrogen bond acceptors in the pyrimidine and piperazine rings of the TPD, 89 , 90 which in turn increase moisture content. It was reported that increasing moisture content results in decreasing the peak temperature of the starch.…”
Section: Resultsmentioning
confidence: 99%
“…Starch, which is highly hygroscopic, can absorb water and be a reservoir of water for hydrolysis processes [ 20 , 21 ]. To complicate the scenario, other excipients, such as lactose, magnesium stearate, and talc, could react with molecules containing amino groups and cause a browning phenomenon [ 22 , 23 , 24 , 25 , 26 ], as well as cocrystallization with compounds such as urea [ 27 ].…”
Section: Introductionmentioning
confidence: 99%